Impact of Anthropogenic Pressure on the Biomass and Productivity of Forest Floor Vegetation in a Submontain forest of Tarai of Kumaun Himalaya - Joshi, Bhasker; Pant, S. C. (Indian Forester, 2012)
The study was conducted to find out impact of anthropogenic pressure on the biomass and productivity of forest floor vegetation in a submontane forest of Tarai of Kumaun Himalaya adjacent to Kashipur. The vegetation was studied at monthly intervals from April 2007 to April 2008 at two selected sites, site I and site II. Aboveground green biomass, aboveground dead biomass, belowground biomass and litter biomass were higher at site II (Gulzarpur forest). Similarly aboveground primary production, belowground production and total net primary production were recorded higher at site II, but litter production was higher at site I (Jogipura forest). Aboveground and belowground turn over was maximum recorded at site II but litter turn over was maximum recorded at site I. Based on the study, it is concluded that the forest at site I which suffer from anthropogenic pressure have low biomass and net primary productivity.